Postpartum acute stress disorder symptoms, social support, and quality of couple’s relationship associations with childbirth PTSD - Handelzalts, Jonathan E.; Kalfon-Hakhmigari, Maor; Raichin, Adi; Peled, Yoav (Frontiers in Psychiatry, 2024)
Background: We aimed to examine the hypothesized negative associations between childbirth post-traumatic stress disorder (PTSD) symptoms (using the two-factor of birth-related and general symptoms), with social support, and couple's relationship quality at 8-12 weeks postpartum, while considering the longitudinal positive shared variance with acute stress disorder (ASD) symptoms measured shortly after birth, considering obstetric and demographic variables. Methods: Participants were 246 mothers who gave birth at the maternity ward of a tertiary healthcare center. Self-report questionnaires were used a1-4 few days postpartum (T1): Demographic information, the Birth Satisfaction Scale-Revised (BSS-R), and the National Stressful Events Survey Acute Stress Disorder Short Scale (NSESSS). At T2 (8-12 weeks postpartum): The Multidimensional Scale of Perceived Social Support (MSPSS), the Dyadic Adjustment Scale (DAS-7), and the City Birth Trauma Scale (BiTS).Results: In partial support of our hypotheses, three hierarchical regression analyses revealed a significant positive contribution of ASD symptoms to childbirth PTSD general symptoms (β = .33, p < .001) and the total score (β = .29, p < .001) but not for birth-related symptoms. Social support (β = -.21, p = .003) and quality of couple's relationship (β=-.20, p = .003) had negative associations with the BiTS general symptoms.Conclusions: Our study enhances understanding of the shared variance between childbirth ASD and PTSD, supporting the factor structure of general and birth-related symptoms as different aspects of childbirth PTSD, and highlighting the negative